2022
DOI: 10.3390/ijms23084265
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Computational Logic Using Toehold Switches

Abstract: The development of computational logic that carries programmable and predictable features is one of the key requirements for next-generation synthetic biological devices. Despite considerable progress, the construction of synthetic biological arithmetic logic units presents numerous challenges. In this paper, utilizing the unique advantages of RNA molecules in building complex logic circuits in the cellular environment, we demonstrate the RNA-only bitwise logical operation of XOR gates and basic arithmetic ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 98 publications
0
6
0
Order By: Relevance
“…Higher sensitivity can only be achieved when multiple biomarkers are present in an AND logic and within predefined threshold limits . Several studies have demonstrated the feasibility of cellular computation. , The future of biomolecule-mediated computing may not be a replacement for silicon, but the use of the inherent advantages of programmable biomolecule-mediated computing to interface with native DNA or in vivo is ideally suited to unlock new medical technologies.…”
Section: Discussionmentioning
confidence: 99%
“…Higher sensitivity can only be achieved when multiple biomarkers are present in an AND logic and within predefined threshold limits . Several studies have demonstrated the feasibility of cellular computation. , The future of biomolecule-mediated computing may not be a replacement for silicon, but the use of the inherent advantages of programmable biomolecule-mediated computing to interface with native DNA or in vivo is ideally suited to unlock new medical technologies.…”
Section: Discussionmentioning
confidence: 99%
“…Several natural riboswitches that detect various small molecules to regulate numerous numbers of genes have been identified both in prokaryotic and eukaryotic organisms. ,, Toehold switches, on the other hand, are de-novo-designed riboregulators that control gene expression via base pairing with target RNA sequences. , These RNA-based sensory and regulatory systems have gained scientific interest due to their capacity to be engineered as sensors for various applications, both in vivo and in vitro. Combined with cell-free protein synthesis systems, engineered RNA switches demonstrated the effectual dynamic range and orthogonality as genetic circuit elements. , Even though several outstanding riboswitch and toehold-based sensors have been developed with low crosstalk, high efficiency, and low background activity; design and validation are still challenging due to variability in function. , …”
Section: Riboregulators and Toehold Switchesmentioning
confidence: 99%
“…RNA-based circuits have several examples, including the incoherent feedforward loop (IFFL) circuit that allows for precise temporal control of gene expression, 24 the exclusive OR (XOR) circuit that can function as a biological switch by controlling the expression of two genes in a mutually exclusive manner, 25 and the cell-free coherent feedforward loop (CFFL) circuit, which can operate outside of living cells and have potential applications in biotechnology and medical diagnostics due to its potential to filter out noise in gene expression via reducing leakage and increasing the fold-change of the output in synthetic genetic circuits. 26 Overall, RNA-based genetic circuits have numerous advantages over protein-based circuits, including better design flexibility, reduced cellular load, and the ability for self-assembly, making them a promising tool for synthetic biology research and applications.…”
Section: Riboregulators and Toehold Switchesmentioning
confidence: 99%
See 1 more Smart Citation
“…Bioinformatic studies of repetitive DNA sequences in Drosophila melanogaster polytene chromosomes show that chromatin structure plays a crucial role in the regulation of gene activity [7]. Recent advances reported by Choi et al demonstrate that nucleic acids may provide useful tools for building complex logic circuits [8]. Finally, for this grouping of articles, Víglaský explores the organization of genetic information in nucleic acids using a novel orthogonal representation, which proves to be useful in predicting the likelihood of particular regions of nucleic acids to form non-canonical motifs [9].…”
mentioning
confidence: 99%